(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Many firms have closed as a consequence of the COVID-19 outbreak, causing substantial trade disruptions practically in every sector of the global economy. Even though the entire supply chain has been damaged by the shutdown. Small or Medium Sized Enterprises have been hit the hardest by virus prevention efforts due to their particular characteristics. The purpose of this study is to investigate how these firms managed with disruptions triggered by closure in term of the employees or their daily routines to keep their operations running. During the lockdown in Portugal, a qualitative approach (descriptive or inductive) was used to achieve this goal, which included snowball sampling and a questionnaire. It also underlined the need for government policies to aid small businesses now and in future. Even though the numeral of businesses observing to them is strongly determined by the eligibility restrictions or the speeds with which institution react. The study’s main contribution is to show SMEs’ weaknesses, such as a lack of capital, human resources, digitalization, are the fundamental hindrance to a meaningful response to the crisis. The distinctiveness of these contributions is since the managers of these businesses possess additional talents or qualities, such as the dynamic capacities to manage a firm in extraordinary crises or to continue functioning even in the face of a worldwide blockade. The findings reveal that SMEs confront a slew of challenges as a result of operational interruptions, which have resulted in significant liquidity issues, threatening future continuity and job security.